Zhodnocení finanční situace podniku - Dobešková, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Bakalářská práce se věnuje finanční situaci firmy Vodohospodářské stavby Javorník – CZ, s.r.o. za roky 2016 – 2020. V teoretické části se věnuji metodám, které budou užity při stanovování finančního zdraví společnosti. V analytické části jsou metody aplikovány na data z účetních výkazů ke zhodnocení současného stavu firmy. Na základě vypočtených hodnot vzniká část návrhová, kde navrhuji doporučení k případnému zlepšení.

The bachelor thesis focuses the financial situation of the company Vodohospodářské stavby Javorník-CZ, s.r.o. between 2016 and 2020. The theoretical part explains the methods that are going to be used in determining the financial health of the company. In the analytical part of the bachelor’s thesis, the methods are to be applied to evaluate the current situation of the company based on the financial records data. The final part of the thesis, where the solution is proposed, is based on calculated data and deals with possible improvement recommendations.
Evaluation of the Financial Situation of a Company
Keywords: Finanční analýza; likvidita; aktivita; rentabilita; strategické modely; 7S; Tafflerův bankrotní model; rozdílové ukazatele; Financial analysis; liquidity; activity; profitability; strategic model 7S; Taffler’s bankruptcy model; differential indicators